Frizzled receptors (FZDs) in Wnt signaling: potential therapeutic targets for human cancers - Liu Hui-yu; Sun Xiao-jiao; Xiu Si-yu; Zhang Xiang-yu; Wang Zhi-qi; Gu Yan-lun; Yi Chu-xiao; Liu Jun-yan; Dai Yu-song; Yuan Xia; Liao Hua-peng; Liu Zhen-ming; et al. (Acta Pharmacologica Sinica, 2024)
Frizzled receptors (FZDs) are key contributors intrinsic to the Wnt signaling pathway, activation of FZDs triggering the Wnt signaling cascade is frequently observed in human tumors and intimately associated with an aggressive carcinoma phenotype. It has been shown that the abnormal expression of FZD receptors contributes to the manifestation of malignant characteristics in human tumors such as enhanced cell proliferation, metastasis, chemotherapy resistance as well as the acquisition of cancer stemness. Given the essential roles of FZD receptors in the Wnt signaling in human tumors, this review aims to consolidate the prevailing knowledge on the specific status of FZD receptors (FZD1–10) and elucidate their respective functions in tumor progression. Furthermore, we delineate the structural basis for binding of FZD and its co-receptors to Wnt, and provide a better theoretical foundation for subsequent studies on related mechanisms. Finally, we describe the existing biological classes of small molecule-based FZD inhibitors in detail in the hope that they can provide useful assistance for design and development of novel drug candidates targeted FZDs.